SIGNS OF INTIMACY AND DISAGREEMENT IN TEXTS OF UYGHUR PERIOD - Uzun, Tuba (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
In human’s life, there are various feelings which express connections between living being, objects and humans. It is possible to say we can show these feelings in two main sections; intimacy and disagreement... In expressing every feeling, people use a lot of symbols and signs. In this study we tried to express verbal signs of intimacy and disagreement in texts of Uyghur period.